O discurso religioso no processo migratório para o caldeirão do beato José Lourenço - Silva, Lemuel Rodrigues da (2009)
The Caldeirão is a site located in the city of Crato, in the south of Ceará, belonged to priest Cícero Romão Batista. There, was created a religious community led by blessed José Lourenço, who marked the life of thousands of Northeast country people in 1930s, for represent to them a space of religious conviviality, work and devotion. The Caldeirão s population was about three thousand of people, originated from states of Pernambuco, Alagoas, Paraíba, Maranhão, Piauí, Ceará and Rio Grande do Norte, who share the community s daily activities. The misery caused by the dryness and exploration of these country people by the landlords are indicated as the motivator elements of this migratory flux by the greater number of works published about the Caldeirão, turning the community into a primitive experience of class struggles. This present study proposes other comprehension of this migratory movement by the religious speech of salvation taken to country people by the counselor Severino Tavares. Was used as analysis camp the remaining norte-rio-grandenses that migrated to the Caldeirão, and as theoretical and methodological references the understanding model of investigation, the cultural history and the remaining memorial speech analysis. The work follows that pointing the phenomenon of Caldeirão as an campestral revolt is try to impose to this people the aspirations or wishes of others, besides of deny to them the right and the dignity of act by their believes and their own dreams.